Beyond Culture: Helping International Students Avoid Plagiarism - Adhikari, Soni (Journal of International Students, 2018)
With the rapid increase in the number of international students from different academic backgrounds around the world, college and university teachers in the West find it harder to understand the many and complex reasons when these students plagiarize or use sources ineffectively. Reviewing relevant literature, I first make a pedagogical analysis of student plagiarism then show why teachers should shift focus from traditional views about cultural difference toward a multidimensional understanding of plagiarism. I conclude by recommending pedagogical strategies to help students to adjust to the new academic system rather than “policing” their activities and undermining their confidence.